Penggunaan Media Pembelajaran untuk Menunjang Proses Pembelajaran PAI dan Budi Pekerti di SMP 1 Tilatang Kamang - Riadi, Ekta; Charles, Charles; Arifmiboy, Arifmiboy; Junaidi, Junaidi (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2023)
This research is motivated by various problems found by the author, such as in learning Islamic education at SMP N 1 Tilatang Kamang where students are required to listen to material from the teacher, no teacher displays media that discusses the learning and the education system only uses lecture and question and answer where in the 2013 curriculum most of the students were active and looking for their own lessons, the teachers only explained what they didn't understand. Research on the use of Islamic education learning media to support the learning process of Islamic education and good manners at SMP N 1 Tilatang Kamang. The type of research that the author uses is descriptive qualitative research aimed at describing and mapping facts based on a certain perspective or framework of thinking. The method that the author uses in this study is a qualitative method by describing, with the informants of this study being the teacher of Islamic education as the key informant, and the 1.1 grade students of SMP N 1 Tilatang Kamang. Data collection tools that the author uses are observation, interviews, and documentation. The results of the research on the use of Islamic education learning media to support the learning process of Islamic education and character education at SMP N 1 Tilatang Kamang. After interviewing the PAI subject teacher he said the media we used were blackboard media and picture media and the teacher prepared lesson plans and the teacher prepared media such as blackboard media. media images and broadcast materials due to the lack of existing facilities in schools.